Squatting with dignity - Kumar, Alok (New Delhi, 2011)
This book provides an analytical view of the successes and challenges encountered while creating the fast expanding rural sanitation movement in India, with a special focus on the last decade.
Keywords: "Sanitation, Rural-India"